An organizational learning approach to process innovations the extent and scope of diffusion and adoption in management accounting systems - Seleshi Sisaye, 1951-; Birnberg, Jacob G. (Studies in managerial and financial accounting ;, 2012)
This book discusses the organizational processes and structural barriers to the diffusion and adoptions of innovations. In this chapter, we address the question of "why innovations fail?"; addresses the organizational learning strategies of adoption and diffusion of process innovation approaches; presents the theoretical framework of organizational learning and process innovations; covers the four typologies of innovations in detail and research questions relating to these four typologies; compares mechanistic and organic innovations, and organizational development (OD) and organizational transformation (OT) innovations; elaborates the organizational learning framework by incorporating the two stages in sociological theories of process innovations: adoption and diffusion.